PaxVax CVD 103-HgR single-dose live oral cholera vaccine. (4th March 2017) - Levine, Myron M.; Chen, Wilbur H.; Kaper, James B.; Lock, Michael; Danzig, Lisa; Gurwith, Marc
ABSTRACT: Introduction: Cholera remains a problem in developing countries and a risk for travelers. Hypochlorhydria, blood group O, cardiac and renal disease increase the risk of developing cholera gravis. Oral vaccines containing inactivated Vibrio cholerae and requiring two doses are available in some countries. No cholera vaccine had been available for U.S. travelers for decades until 2016 when CVD 103-HgR (VAXCHORA™), an oral live attenuated vaccine, was licensed by the U.S. FDA. Areas covered: Enduring protection following wild-type cholera provided the rationale to develop a single-dose live oral vaccine. CVD 103-HgR is well-tolerated and protects against cholera caused by V. cholerae O1 of either serotype (Inaba, Ogawa) and biotype (El Tor, Classical). Since 90% vaccine efficacy is evident 10 days post-ingestion of a single dose, CVD 103-HgR can rapidly protect travelers. Vibriocidal antibody seroconversion correlates with protection; >90% of U.S. adult (including elderly) vaccinees seroconvert. The U.S. Public Health Service's Advisory Committee on Immunization Practices recommends CVD 103-HgR for U.S. travelers to areas of ongoing cholera transmission. Expert commentary: Next steps include evaluations in children, post-licensure safety and effectiveness monitoring, diminishing cold chain constraints, optimizing a 'high-dose' formulation for developing countries, and diminishing/eliminating the need for water to administer a dose.